Financial inclusion and the performance of banking sector in Palestine - Saleh F. A. Khatib; Ernie Hendrawaty; Ayman Hassan Bazhair; Ibraheem A. Abu Rahma; Hamzeh Al Amosh (Economies, 2022)
Despite evidence on the social and economic importance of financial inclusion (FI), the relationship between FI and bank profitability remains unclear. In this research, we evaluated the association between financial inclusion and the performance of banks in Palestine using dynamic panel analysis applied to a sample of 11 banks, with two econometric models representing profitability indicators over a nine-year period (2012-2020). In addition to linear regression models, the generalized method of moments estimator was utilized. The results showed that access to financial services (e.g., the number of automated teller machines (ATMs) and the number of bank branches), service delivery (including the average costs to maintain a current account), and the quality of the products improve banks' profitability. However, point-of-sale terminals have no impact on profitability. Additionally, financial service utilization reflected in bank account number sand credit to small and medium-sized enterprises do not affect bank profitability, and among bank-specific variables, the nonperforming loan ratios, the cost-to-income ratios, and liquidity were found to be the main drivers of profitability. Policymakers in Palestine must prioritize FI by adopting rules that encourage lending to practices of financial institutions.
Keywords: 330; ATMs; bank performance; branches; financial inclusion; Palestine